Pengaruh Kualitas Produk, Kepuasan Pelanggan Dan Harga Terhadap Loyalitas Pelanggan, Handphone Samsung (Studi Kasus Di Fakultas Ekonomi Ums) - Rizaldi, Novizar, Drs. Sujadi, MM (2017)
The purpose of this study to determine the effect of product quality, customer satisfaction and price to customer loyalty Samsung Mobile (Case Study at Faculty of Economics UMS). The research method used the population of this study were students and students Muhammadiyah Surakartayang using Samsung Mobile, with a sample of 100 respondents. Sampling method using Accidental sampling, The technique of termining the sample by chance, ie who happens to meet with the researcher can be sampled if deemed suitable. The analysis results obtained (1) that Product Quality affects customer loyalty. This shows the first hypothesis that states "Suspected Product Quality affects customer loyalty" is proven true. (2) Customer Satisfaction affect customer loyalty. This shows a second hypothesis that states "Suspected Customer Satisfaction affects customer loyalty" is proven, and (3) price affects customer loyalty. This shows a third hypothesis that states "Suspected Price affects customer loyalty" is proven true.